Achieving visible-light-excited organic room-temperature phosphorescence by manipulating p–π conjugation. Issue 41 (11th October 2021) - Xu, Qingyang; Ma, Liangwei; Sun, Siyu; Ma, Xiang
Abstract : Achieving visible-light-excited room-temperature phosphorescence by changing the sizes of the heterocyclic ring to manipulate p–π conjugation in the molecular structure. Abstract : The development of organic room-temperature phosphorescence (RTP) materials has been a rich research field. However, there are still limited practical and directive strategies to regulate the phosphorescence emission. Herein, six naphthalene-based thiochromanone analogs with different heterocycles were synthesized. And all these molecules exhibited bright phosphorescence when embedded into a polyvinyl alcohol matrix under ambient conditions. The absorption spectra showed a distinct red-shift as the size of the heterocycle shrunk, which resulted from the facilitated p–π conjugation. In particular, the absorption spectra of molecules with a five-membered heterocycle were extended to visible light, which is rarely reported for RTP materials. These results might present a new strategy to adjust the photophysical properties of phosphors to obtain phosphorescence materials with the desired excitation and emission wavelength.